Distribusi Penerapan Strategi Marketing Public Relations (MPR) dalam Event SPMB SMAN 1 Nguntoronadi - Rahmat Wisudawanto; Dina Gustiani; Rizka Nur Hidayati; Tarangga Fathanah F. P.; Fidelia Zhafirah Pratiwi; Raihan Ammar Fauzi (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2026)
The development of digital media has changed the way educational institutions communicate with the public. Instagram is one of the platforms utilized by schools to deliver information while simultaneously building institutional image through social media content. This study aims to analyze the implementation of Marketing Public Relations (MPR) strategies in the Instagram content of SMA Negeri 1 Nguntoronadi during the 2026 New Student Admission System (SPMB). This research employed a descriptive method with a qualitative approach using content analysis techniques. The research data were obtained from 21 official Instagram posts of @sman1nguntoronadi related to the 2026 SPMB activities. The analysis was conducted by categorizing the content based on three MPR strategies, namely Push Strategy, Pass Strategy, and Pull Strategy. The results showed that the most dominant strategy used was the Push Strategy with a percentage of 47.62%, followed by the Pass Strategy at 28.57%, and the Pull Strategy at 23.81%. These findings indicate that Instagram of SMA Negeri 1 Nguntoronadi is primarily used as a medium for delivering technical information related to the new student admission process. In addition, the Pass and Pull Strategies also contribute to building public trust and increasing the attractiveness of the school. This study demonstrates that well-planned Instagram content management can support school public communication functions, not only as an information medium but also as a tool for establishing a positive institutional image.